2020
DOI: 10.1186/s12974-020-01833-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent involvement of gut mast cells and histamine in post-stroke inflammation

Abstract: Background: Risk of stroke-related morbidity and mortality increases significantly with age. Aging is associated with chronic, low-grade inflammation, which is thought to contribute to the poorer outcomes after stroke seen in the elderly. Histamine (HA) is a major molecular mediator of inflammation, and mast cells residing in the gut are a primary source of histamine. Methods: Stroke was induced in male C57BL/6 J mice at 3 months (young) and 20 months (aged) of age. Role of histamine after stroke was examined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…In addition to the brain, stroke can also cause inflammation in other locations, such as the gut and blood ( Spychala et al., 2018 ; Blasco et al., 2020 ). Many studies have found that inflammatory mediators are elevated after stroke, including IL-17a ( Waisman et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the brain, stroke can also cause inflammation in other locations, such as the gut and blood ( Spychala et al., 2018 ; Blasco et al., 2020 ). Many studies have found that inflammatory mediators are elevated after stroke, including IL-17a ( Waisman et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“… 31 Our results link down-regulation of resting mast cells with greater risk of ischemic stroke. Animal models of ischemic stroke showed elevated numbers of activated mast cells, and activation of mast cells can increase angiogenesis by increasing proinflammatory monocyte responses, 32 , 33 which in turn can promote the progression of diabetes and increase risk of ischemic stroke. 4 , 34 Our work may help guide further research into how immune cell changes, immune responses, and inflammatory events interact to contribute to ischemic stroke in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% of immune cells were pooled in the gut, where the balance of the peripheral T lymphocytes was skewed toward pro-inflammatory cells after ischemic stroke, from where the lymphocytes migrate to the cerebral infarction area. The histamine (HA)/gut histamine receptor mediated the elevation of pro-inflammatory factors [IL-6, TNF-α, Interferon-gamma (IFN-γ), and granulocyte-colony stimulating factor (G-CSF)] in the gut, facilitating the differentiation into pro-inflammatory T cells ( 112 ). The gut microbiota dysbiosis also abolished the ability of Dendritic cells (DCs) to drive Treg differentiation and promoted the ability of DCs to induce γδT cell differentiation ( 113 ).…”
Section: Role Of Peripheral Immune Cells In the Disruption Of Bbb In Strokementioning
confidence: 99%